Amtshaftung Prozesstypische Aspekte und Fragestellungen - Rohlfing, Bernd (Universitätsverlag Göttingen, 2017)
Should court officers cause damage to third parties in performance of their duties, these damages are often claimed as public law cases in which the responsibilities are transferred to the state. The liability of public authorities according to § 839 section 1 sentence 1 German Civil Code in conjunction with Art. 34 sentence 1 German Basic Law is part of state liability law. However, public liability law is a Janus-faced area of legal material. Systematically, it belongs to administrative law, and by that to public law. Nonetheless, a government liability suit is a civil courts domain. When it comes to public liability suits, there are many intrinsic issues arising from special rules of civil courts jurisdiction in these matters. The examination at hand enlightens - by no means exhaustive - questions prior to public liability cases and specific problem constellations in matters of admissibility and merits of legal action for public liability claims.